PATERNITY LEAVE: FIRST RESULTS OF INTRODUCTION IN MOLDOVA - Inga Chistruga — Sînchevici (Economy and Sociology, 2022)
Parental leave policies are important instruments regulating how the men’s and women’s concurrent role as parents and employees is valued and encouraged. Although paternity leave in Moldova was introduced in 2016, the share of fathers who benefit from this leave remains low.